- #1

Wiemster

- 72

- 0

with S and S' elements of the subgroup H of G we then have that if a certain element X of the group G belongs to the coset TH but to T'H as well

i.e. X=TS=T'S' we should have that T=T' right?

This means TS(S'^-1)=T'E with S(S'^-1) again an element of H, but I don't see why T should be T', or did I misintepreted the theorem?

(PS: Somewhat further they use as an example a generelaized torus:

**R**

^{n}/

**Z**

^{n}= (

**R**/

**Z**)

^{n}which is supposed to b homomorphic to the unit circle. But I don't really see what this 'factor group' represents... )